THE EFFECT OF SERVICE QUALITY PROMOTION AND MOTIVATION ON THE DECISION TO CHOOSE GOLD SAVINGS PRODUCTS AT PT. PEGADAIAN (PERBAUNGAN BRANCH) - Yanti, Yusri Irma; Hidayat, Rahmat (SEAN Institute, 2023)
The purpose of this study is to determine whether there is an influence of promotion, service quality and motivation on the decision to choose gold savings products at PT. Pawnshop. The sample of this study was 144 customers. Sampling uses accidental sampling or chance sampling, that is, anyone who accidentally meets with the researcher can be used as a sample. Data analysis uses Multiple Regression test, hypothesis testing uses coefficient of determination test (R2), partial test (t test), simultaneous test (F test), while data processing uses SPSS 22. The results showed that partially the promotion of service quality and motivation influenced the decision to choose, and simultaneously the promotion of service quality and motivation had a positive and significant effect on the decision to choose